Histopathology of oral lichen planus and oral lichenoid lesions: An exploratory cross‐sectional study. (4th January 2022) - Lodolo, Michele; Gobbo, Margherita; Bussani, Rossana; Torelli, Lucio; Rupel, Katia; Ottaviani, Giulia; Poropat, Augusto; Biasotto, Matteo
Abstract: Objective: To better characterize the histopathology of oral lichen planus and oral lichenoid lesions and to highlight the differences between them in order to support the clinician in the diagnostic and therapeutic management of such conditions. Subjects and Methods: Fifty‐five patients, clinically diagnosed with oral lichen planus ( n = 25) or oral lichenoid lesions ( n = 30), were consecutively enrolled in the present study. Subsequently, one blind pathologist reviewed all the biopsy specimens of enrolled subjects following a specific protocol to provide a detailed histopathological description. Demographic, anamnestic, and clinical data were also recorded from all the participants. Patients' data were analysed and compared using the chi‐squared test, to provide distinguishing features between the studied conditions. Results: We found a higher and statistically significant number of eosinophils in the oral lichenoid lesions compared with the oral lichen planus group ( p < 0.01), an equally promising result was seen regarding plasma cells, which were more represented ( p = 0.05) in the oral lichenoid lesions than in the oral lichen planus cases. No statistically significant differences were detected in demographic, anamnestic and clinical data. Conclusion: A mixed lichenoid inflammatory infiltrate, consisting of eosinophils and plasma cells, could be used as reliable histological features for the diagnosis of oral lichenoid lesions, as long as compared with findings obtained from the patients' history and clinical examination.